2017
DOI: 10.1017/ice.2017.134
|View full text |Cite
|
Sign up to set email alerts
|

Variable Case Detection and Many Unreported Cases of Surgical-Site Infection Following Colon Surgery and Abdominal Hysterectomy in a Statewide Validation

Abstract: OBJECTIVETo assess hospital surgical-site infection (SSI) identification and reporting following colon surgery and abdominal hysterectomy via a statewide external validationMETHODSInfection preventionists (IPs) from the California Department of Public Health (CDPH) performed on-site SSI validation for surgical procedures performed in hospitals that voluntarily participated. Validation involved chart review of SSI cases previously reported by hospitals plus review of patient records flagged for review by claims… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 17 publications
(27 reference statements)
1
18
0
Order By: Relevance
“…Indeed, detection of SSI cases, based on claims data that might have been omitted during routine surveillance, may be used as an initial screening technique, prior to the more rigorous investigation of medical records [18]. Calderwood et al [19] assessed regularly collected electronic Medicare claims data to obtain postoperative SSI data. He developed an SSI indicator coding system for specific surgeries and found that SSI detection rate, based on claims data, was approximately 1.8-4.7 times higher.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, detection of SSI cases, based on claims data that might have been omitted during routine surveillance, may be used as an initial screening technique, prior to the more rigorous investigation of medical records [18]. Calderwood et al [19] assessed regularly collected electronic Medicare claims data to obtain postoperative SSI data. He developed an SSI indicator coding system for specific surgeries and found that SSI detection rate, based on claims data, was approximately 1.8-4.7 times higher.…”
Section: Discussionmentioning
confidence: 99%
“…Different approaches in the inclusion and exclusion criteria have been widely described in the literature and have the potential to result in overreporting or underreporting of certain diagnoses. 36 This could occur because of the differences in coding standards specific to the United States institutions and result in a limited number of diagnoses, which could be listed per patient. These differences have the potential to be particularly challenging for any scientific study because of the financial penalties imposed by the Centers for Medicare and Medicaid Services (CMS) for hospital-acquired conditions that rely on the diagnosis codes and, therefore, may incentivize underreporting of ICD-9 codes associated with SSIs.…”
Section: Discussionmentioning
confidence: 99%
“…34,35 Data indicate that currently used ACD, specifically ICD-9 coding, may have limited and variable accuracy for the identification and surveillance of hospital-acquired infection. In a recent study 36 conducted at 47 acute care hospitals in California, researchers looked at both traditional surveillance and claims-based surveillance for surgical site infection. These researchers found that the overall sensitivity for traditional surveillance was 50% whereas that of claims-based surveillance was 84%, and that surveillance using both ICD-9 and ICD-10 codes provided a standardized approach.…”
Section: Limitationsmentioning
confidence: 99%
“…These researchers found that the overall sensitivity for traditional surveillance was 50% whereas that of claims-based surveillance was 84%, and that surveillance using both ICD-9 and ICD-10 codes provided a standardized approach. 36 Nevertheless, given that the identification of surgical site infection can occur in either the acute care setting before discharge or in the outpatient setting where the surveillance process is less defined, these findings may have limited applicability for the acute care infection surveillance used to identify NV-HAP.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation